2003
DOI: 10.1046/j.1442-2042.2003.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effective laparoscopic pyeloplasty: Single center experience

Abstract: SummaryObjective : Laparoscopic pyeloplasty (LPP) is a minimally invasive treatment option for ureteropelvic junction (UPJ) obstruction. We report here our experience of performing cost-effective LPP on 24 patients at a single center. Methods : Between October 1999 and March 2002, LPP was performed in 24 patients (17 male, seven female; age range 8-51 years) including two patients who had failed previous endourologic treatments. In two patients with concomitant renal stones, laparoscopic pyelolithotomy was als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…We had reported that most UPJ obstructions can be cost-effectively managed laparoscopically including those that have failed endopyelotomy or have a dilated renal pelvis, coexisting renal calculous disease, abnormalities of position or rotation, and those with associated crossing vessels. 2 Although the laparoscopic technique mimics open surgery, it is not as versatile, however, and it becomes technically more challenging in cases of failed pyeloplasty. With the availability of the robot at our institute, we explored its potential use in these difficult situations.…”
Section: Discussionmentioning
confidence: 99%
“…We had reported that most UPJ obstructions can be cost-effectively managed laparoscopically including those that have failed endopyelotomy or have a dilated renal pelvis, coexisting renal calculous disease, abnormalities of position or rotation, and those with associated crossing vessels. 2 Although the laparoscopic technique mimics open surgery, it is not as versatile, however, and it becomes technically more challenging in cases of failed pyeloplasty. With the availability of the robot at our institute, we explored its potential use in these difficult situations.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson-Hynes pyeloplasty, as described by us earlier [3]. The pyeloplasty was then performed with intra-corporeal free hand suturing using ordinary 4-0 Vicryl suture.…”
Section: Techniquementioning
confidence: 99%
“…Medical literature is filled with articles about endoscopic surgery that address topics such as cost‐effectiveness, 11,30–34 identification of surgical procedures that benefit from endoscopic technique, 35 , 36 outcome data, 37 , 38 and surgical patient selection 39 , 40 . Many investigators have reported favorable outcomes for patients undergoing MIS procedures, including reduced surgical times, and decreased hospital stays even for patients who have complicated injuries or disease processes 36–38 .…”
Section: Behavioral Objectivesmentioning
confidence: 99%